Exploring EFL Students’ Experiences of Learning Intensity in Speaking Practice - Aisyah Dita Zhaqila; Mochlis Ekowijayanto (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
This study explores how junior secondary EFL students experience learning intensity during speaking practice in the English Time program at MTsN 1 Probolinggo, Indonesia. Rather than treating intensity as task frequency or duration, the study conceptualizes it as a multidimensional experience shaped by cognitive effort, emotional pressure, social visibility, and strategic regulation. Using a qualitative case study design, data were collected over four weeks through classroom observations, semi-structured interviews with six focal participants, students’ reflective journals, and researcher memos. The data were analyzed using reflexive thematic analysis. Four interrelated themes emerged. First, public performance intensified speaking practice because students felt exposed to peer gaze, teacher evaluation, and possible public mistakes. Second, cognitive overload occurred when students treated speaking as a fixed sequence of accurate words and sentences, while learners who used ideas and keywords showed greater flexibility. Third, intensity was emotionally framed either as a threat or as a productive challenge, depending on students’ confidence and perceived classroom safety. Fourth, memorization functioned as the dominant regulation strategy. Full-script memorization reduced anxiety and prevented silence, but it also limited spontaneity when students forgot part of the script. In contrast, keyword-based preparation supported more flexible communication. This study extends EFL speaking, engagement, and willingness-to-communicate research by positioning learning intensity as a socially mediated, cognitively negotiated, emotionally filtered, and strategically managed classroom experience. Pedagogically, the findings suggest that speaking activities should be challenging yet emotionally safe, gradually guiding students from rigid memorization toward keyword planning, guided paraphrasing, peer-supported rehearsal, and spontaneous communication.